Among friends : engendering the social site of poetry - Dewey, Anne Day; Rifkin, Libbie (Contemporary North American poetry series., 2013)
Philosophers and theorists have long recognized both the subversive and the transformative possibilities of friendship, the intimacy of which can transcend the impersonality of such identity categories as race, class, or gender. Unlike familial relations, friendships are chosen, opening a space of relative freedom in which to create and explore new identities.